Formaldehyde sensor based on FSP-made AgOx-doped SnO2 nanoparticulate sensing films - K. Khamfoo (2020)
© 2020 Elsevier B.V. In this research, 0–1 wt% AgOx-doped SnO2 nanoparticles were developed based on a single-step flame spray pyrolysis process and investigated for formaldehyde (HCHO)-sensing applications. The structural evaluations by X-ray diffraction, X-ray spectroscopy, electron microscopy, nitrogen adsorption and optical absorption indicated that Ag species containing Ag+ and Ag2+ oxidation states could be embedded in 5–20 nm tetragonal SnO2 nanoparticles as secondary AgOx crystals, leading to smaller crystallite size, larger surface area and smaller optical bandgap. From gas-sensing measurements at 200–400 °C, AgOx-doping with an optimal Ag content of 0.2 wt% enhanced HCHO response by more than one order of magnitude compared with that of undoped one. In particular, the 0.2 wt% AgOx-doped SnO2 sensing films exhibited a high response of ∼495–2000 ppm HCHO at 350 °C with high selectivity against NH3, NO, C2H2, C2H4, H2, CH4, C3H6O, C6H6, C2H6O, CH3OH, C7H8 and C8H10. Moreover, the AgOx doped SnO2 sensors displayed good stability and low dependencies of response on temperature and humidity. Thus, the FSP-made 0.2 wt% AgOx-doped SnO2 sensor could be a promising choice for selective and sensitive HCHO detections.